Mapping Constraints of Art Extracurricular in Indonesia as An Effort of Policy Design - Herdiati, Dian; Saputra, Dani Nur (Harmonia: Journal of Arts Research and Education, 2021)
Extracurricular arts programs are an integral part of instilling character qualities in students. This research aimed to map out the constraints to extracurricular arts in elementary schools in Indonesia. To achieve the goal, this research looks at government initiatives aimed at enhancing the standard of arts extracurricular activities in elementary schools across the Country, which were carried out from 2013 to 2019. The method used in this study is a qualitative method with a participatory observation approach. They were collecting data using participatory methods, observation, and guided discussion. This study’s results indicate that schools’ various obstacles in implementing extracurricular programs, ranging from the availability of competent teachers in the arts, funding constraints for trainers, and the existence of regional autonomy. This constraint mapping is very useful for designing policies and extracurricular programs that are appropriate for schools.